2016
DOI: 10.1038/srep38936
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin A, retinol and carotenoid intake and pancreatic cancer risk: Evidence from epidemiologic studies

Abstract: Pancreatic cancer is a devastating disease with poor prognosis. The association between vitamin A, retinol and carotenoid intake and the risk of pancreatic cancer occurrence remains controversial, and therefore it is necessary to make a meta-analysis to clarify the association between vitamin A, retinol and carotenoid intake and pancreatic cancer risk. In the present study, PubMed and EMBASE databases were used to identify qualified studies. The association between dietary vitamin A, retinol and carotenoids wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 48 publications
(66 reference statements)
2
34
0
2
Order By: Relevance
“…Interestingly, we obtained a consistent result in the cohort studies although we included 5 cohort studies, which is two more than Koushik et al Previous meta-analyses had been published to assess the intake of vitamin A and cancer risk. Huang et al and Zhang et al had explored the association between vitamin A intake and pancreatic cancer [27,28], they obtained a consistent result, which might inversely correlate with pancreatic cancer while with vitamin A intake. Yu et al concluded that higher category of dietary vitamin A intake could reduce the risk of lung cancer [29].…”
Section: Figure 3 Funnel Plot For the Analysis Of Publication Bias Bmentioning
confidence: 80%
“…Interestingly, we obtained a consistent result in the cohort studies although we included 5 cohort studies, which is two more than Koushik et al Previous meta-analyses had been published to assess the intake of vitamin A and cancer risk. Huang et al and Zhang et al had explored the association between vitamin A intake and pancreatic cancer [27,28], they obtained a consistent result, which might inversely correlate with pancreatic cancer while with vitamin A intake. Yu et al concluded that higher category of dietary vitamin A intake could reduce the risk of lung cancer [29].…”
Section: Figure 3 Funnel Plot For the Analysis Of Publication Bias Bmentioning
confidence: 80%
“…Recent studies indicate that lycopene intake has protective functions against cardiovascular diseases by lowering high-density lipoprotein (HDL)-associated inflammation [69]. It was proposed that there is an inverse association between the occurrence of pancreatic cancer and dietary lycopene intake together with vitamin A and β-carotene [70]. β-Carotene 9′,10′-oxygenase which is a key enzyme for the metabolism of lycopene has been proposed to have an important roles to prevent prostate cancer progression by inhibiting NF-κB signaling [71].…”
Section: Antioxidant Functions Of Carotenoids At Molecular Level For mentioning
confidence: 99%
“…Skin carotenoid levels therefore reflect a good diet-rich in fruit and vegetables (Stephen et al, 2011;Whitehead et al, 2012)-but carotenoids could also act as a more general cue to human health. Reduced blood plasma carotenoid levels have been linked to a variety of disease states including HIV infection (Friis et al, 2001), malaria (Das et al, 1996), risk of some cancers (Leoncini et al, 2015;Huang et al, 2016), and myocardial infarction (Street et al, 1994); however, objective measures of health in terms of immune function, sperm status, and oxidative stress in normal adults have not been found to relate consistently to skin carotenoids (Foo et al, 2017a,b;Phalane et al, 2017). Our study explores the relationship between other aspects of health and carotenoid-based skin color.…”
Section: Introductionmentioning
confidence: 99%